Establishing Ex Situ Conservation Methods for Dactylorhiza ebudensis and D. traunsteinerioides, a Combination of In Situ Turf Removal and In Vitro Germinations - Berta Millas Xanco; Jaime V. Aguilar; Gregory J. Kenicer; Heather McHaffie (Sibbaldia, 2012)
Orchidaceae is one of the most diverse flowering plant families in the world, occupying a diverse range of habitats from epiphytes to terrestrial forms. It is also one of the most vulnerable to changes in land use because of its complex ecological requirements. In nature, orchid seed will only grow if infected with a compatible fungus which provides all the carbohydrates and nutrients needed for its development. This mycotrophic mode of nourishment can persist underground for years in some orchids, which makes them difficult to observe in the wild. Understanding their behaviour is essential for their successful propagation and conservation. In an investigation looking into conservation and propagation, turves were lifted from wild populations of two rare Scottish orchid species in order to ensure the best possible association between these species and their growing environment. A combined in vitro experiment was set up for the wild harvested seeds under different media to compare their effects. Two different successful ex situ conservation methods for Dactylorhiza ebudensis and D. traunsteinerioides are presented.